Comparison of Propofol with Butorphanoland Propofol with Fentanyl for Total Intravenous Anaesthesia in Short Surgical Procedures - Aakash Trivedi; Dhavalkumar C Patel (Academia Anesthesiologica International, 2019)
Background: Total intravenous anaesthesia is a technique in which induction and maintenance of anaesthesia is achieved with intravenous drug alone. With analgesics complete anaesthesia can be achieved. Objectives: To study & compare the hemodynamic profile, intra operative analgesic adequacy, VAS score and emergence time between two groups.Subjects and Methods:Total 80 patients of ASA grade I & II, aged 18-60years old, who were posted for short surgical procedures were randomly divided into two groups. Group I received Inj.Butorphanol 20?g/kg and Group II received Inj.Fentanyl 2?g/kg body weight. Both the groups received Inj. Propofol 2mg/kg I.V. and then maintenance of anaesthesia started with Propofol as a stepped down scheme. Intra operative depth of anaesthesia was monitored using clinical signs like rise in blood pressure, pulse and respiratory rate. Post-operative sedation score was noted using Ramsay Sedation score. Visual analogue score for pain, was noted at the time of emergence time.Results:Respiratory rate, heart rate and SpO2 showed no significant differences between groups. Average systolic and diastolic BP in group I was lower as compared to group II during the surgery and post-operative at the time of emergence also. Mean emergence time in group I was significantly higher than group II. Mean VAS at the time of emergence was significant less in butorphanol group.Conclusion: From the present study it can be concluded that, Butorphanol& Fentanyl combined with Propofol are comparable in hemodynamic profile. Post-operative more time is taken for emergence in Butorphanol group. VAS score for pain at the time of emergence is more in Fentanyl group compared to Butorphanol. With conventional monitoring, depth of anaesthesia is satisfactory between groups. With both the drugs satisfactory anaesthesia can be provided for short surgical procedures which are 30 or less in duration.